Intergenerational effects in the diffusion of new technology: The case of mobile phones - Jukka Liikanen; Paul Stoneman; Otto Toivanen (The Research Institute of the Finnish Economy (ETLA), 2002)
Many new technologies exhibit clear generational changes. The empirical literature on technology diffusion traditionally analyses the spread of new technologies generically. We use data from the mobile phone industry, where first-generation (1G) and second-generation technologies (2G) can be clearly identified, to analyse the role of generational effects in diffusion. The results from a generation specific approach differ significantly from those of a generic model. There are positive within-generation network effects. 1G (2G) has a positive (negative) effect on 2G (1G) diffusion. Both generations are substitutes for fixed phones. Effects of competition and payment schemes are also analyzed. – – Useissa uusissa teknologioissa on selviä sukupolvia. Teknologian diffuusion empiirinen kirjallisuus käsittelee kuitenkin perinteisesti vain ns. geneeristen teknologioiden leviämistä. Tässä tutkimuksessa käytämme aineistoa ensimmäisen (1G) ja toisen (2G) sukupolven käsipuhelimista sukupolvien välisten vaikutusten analysoimiseen. Geneerinen ja sukupolvien välisten vaikutukset salliva malli tuottavat hyvin erilaisia tuloksia. Sukupolvien sisältä löytyy positiivisia verkostovaikutuksia. Tuloksemme osoittavat myös, että 1G (2G) vaikuttaa positiivisesti (negatiivisesti) 2G (1G) leviämisnopeuteen. Molemmat sukupolvet ovat substituutteja kiinteille puhelimille. Tutkimme myös kilpailun ja maksukäytäntöjen vaikutuksia.
Keywords: L0; L68; O33; 330; mobile phones; network effects; technology diffusion; technological generations; Innovationsdiffusion; Mobiltelefon; Network Externalities; Welt